Developing a Model of Multiple Intelligence-Based Materials for Teaching English in Elementary School - Murni Wahyanti, C.; Saleh, Mursid; Warsono, Warsono; Rukmini, Dwi (The Journal of Educational Development, 2018)
This study aims at developing multiple-intelligences (MI)-based materials for teaching English in elementary school. It applies the research and development method. In the exploration stage, a needs analysis and a document analysis were carried out. Thirty public elementary school teachers in Semarang filled out a questionnaire. The document analysis was meant to find out to what extent the English learning materials used by most of the teachers addressed the MI theory. In the development stage, the prototype of the model was developed, evaluated by experts and tried-out in one school. In the last stage, a pre-experimental study was carried out in three schools. The results indicated that learning materials which have variations of tasks were needed. The analysis of the learning materials showed that some intelligence types were very rarely represented. As for the prototype of the model, some revisions were required. The result of the t-test indicated that the model was effective for improving the studentsâ English mastery. This study suggests that the model of MI-based materials developed is appropriate for teaching English to elementary school students.